Hybrid Proton Exchange Membrane

By introducing polymers with SO3H and -SH functional groups into the fuel cell membrane to form a proton exchange membrane with self-regeneration properties, the problem of membrane degradation of fuel cells under high temperature and high humidity conditions is solved, and the performance and life of the battery are significantly improved.

CN113161591BActive Publication Date: 2025-04-29シンビオ +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110097630.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-23
Filing Date
2021-01-25
Publication Date
2025-04-29
Estimated Expiration
2041-01-25

AI Technical Summary

Technical Problem

Fuel cells operate under high temperature, extremely low temperature and high relative humidity conditions, resulting in membrane degradation, especially the formation of hydrogen peroxide, causing damage to the material, reducing the service life of the membrane.

Method used

A proton exchange membrane based on a hybrid material is used, which comprises a conductive cathode layer and anode layer, each containing a polymer with SO3H functional groups, and a thiol functional group (-SH) is introduced into the cathode layer in order to react with hydrogen peroxide and maintain the mechanical and conductive properties of the film.

Benefits of technology

The self-regeneration properties consume hydrogen peroxide, prevent it from accumulation, maintain the conductive properties, and significantly improve the performance and life of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113161591B_ABST
    Figure CN113161591B_ABST
Patent Text Reader

Abstract

The present invention relates to a hybrid proton exchange membrane for use in fuel cells, said membrane having self-regenerating properties, as well as to cells comprising said membrane and to a method for their manufacture by electrospinning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells and in particular to proton exchange membranes used in these cells. Background Art

[0002] Proton exchange membranes or polymer electrolyte membranes (PEMs) are semipermeable membranes that allow proton conduction while being impermeable to gases such as dioxygen or hydrogen: protons can pass through the membrane, while gases are blocked. PEMs are usually made of pure polymer membranes or polymer-based composite membranes.

[0003] Fuel cell membranes based on sulfonated copolymers of tetrafluoroethylene and perfluoro(alkyl vinyl ether) are also known. Thus, one of the materials most commonly used by manufacturers of proton exchange membranes is Nafion, a sulfonated fluorinated copolymer produced by DuPont.

[0004] CA2950775 describes a network of electrospun fibers to reinforce fuel cell membranes.

[0005] US 2007 / 0213494 describes organo-mineral (hybrid) polymers based on silica and their use as proton exchange materials.

[0006] However, operation of fuel cells can lead to degradation of the membranes due to high or very low temperatures and high relative humidity (close to 90%) and the formation of hydrogen peroxide (H2O2), which degrades the material.

[0007] Therefore, there is a need to provide an improved membrane that is more resistant to these operating constraints and has a longer service life.

[0008] The invention thus provides a membrane based on a hybrid material based on organic and inorganic components, said membrane being particularly capable of reacting with hydrogen peroxide while maintaining excellent mechanical and conductive properties. Summary of the invention

[0009] According to a first object, the invention relates to a proton exchange membrane for a fuel cell, said membrane comprising an anode face on the anode side and a cathode face on the cathode side, said membrane comprising two layers:

[0010] a conductive and self-regenerating cathode layer providing the cathode face and comprising at least one polymer having SO3H functional groups (iii), and

[0011] a conductive anode layer providing the anode surface and comprising at least one polymer having SO3H functional groups (iii');

[0012] The polymers (iii) and (iii') may be the same or different;

[0013] The membrane is characterized in that the cathode layer comprises at least one polymer (i) having thiol functional groups (—SH).

[0014] According to the invention, the membrane has cathodic SH functional groups, ie the SH functional groups are present in the cathodic layer of the membrane.

[0015] These SH functional groups may also be present in the cathode catalyst layer of the fuel cell.

[0016] Thus, a cell comprising a membrane according to the invention advantageously comprises a zone functionalized with SH functional groups, which zone extends from the cathode layer of the membrane to the cathode catalytic layer present at its surface.

[0017] According to one embodiment, the -SH functional groups may be uniformly distributed within the cathode layer, and optionally within the cathode catalyst layer.

[0018] Alternatively, they may be distributed with a concentration gradient of -SH functional groups increasing towards the cathode surface. The gradient means that the concentration of SH functional groups gradually increases from the inner face of the cathode and anode layers towards their outer face providing the interface with the cathode catalyst layer.

[0019] The term "inner face of the membrane" is understood to mean the interface between the cathode layer and the anode layer.

[0020] The term "external face of the membrane" is understood to mean the cathode face and the anode face thereof, which provide interfaces with the cathode catalytic layer and the anode catalytic layer, respectively.

[0021] The proton exchange membranes according to the invention are self-regenerating because they use harmful hydrogen peroxide that is generated during cell operation and degrades the membrane. The SH functional groups present in the cathode layer (and optionally in the cathode catalytic layer) react and consume hydrogen peroxide, thereby preventing its harmful accumulation. In addition, the reaction produces SO3H functional groups, which maintain the conductive properties or even regenerate and improve the conductive properties.

[0022] The membrane according to the invention therefore makes it possible to significantly increase the performance and lifetime of fuel cells.

[0023] According to one embodiment, these layers are formed from mixed fibers obtained, for example, by electrospinning.

[0024] According to one embodiment, the membranes according to the invention are referred to as hybrid, since they comprise an organic component and an inorganic component (also referred to herein as a mineral component).

[0025] The organic component generally provides the conductive properties, while the inorganic component provides the network.

[0026] Typically, the network is a silicate mineral network, for example of the Nafion type, or for example a sulfonated polyether. Thus, according to one embodiment, the cathode layer and / or the anode layer comprises / comprises an inorganic polymer (ii) and / or (ii'), respectively; the polymers (ii) and (ii') may be identical or different. Preferably, polymers (ii) and (ii') are derivatives of silicon.

[0027] Therefore, the membrane according to the invention combines the use of The membrane has the ability to mimic structural phase separation and possesses oriented ionic nanochannels through which protons can diffuse easily.

[0028] Additionally, the composition of the membrane has a favorable hydrophilicity / hydrophobicity ratio, which improves the diffusion of protons and the wettability of the membrane.

[0029] The morphology and composition of the film provide excellent mechanical properties over a wide temperature range, which can range between negative temperatures and about 120°C.

[0030] According to one embodiment, the membrane according to the invention consists of a mixture of:

[0031] - an organic polymer selected from polymers (i) having SH functional groups and / or polymers (iii) and (iii') having SO3H functional groups, and

[0032] - Inorganic polymers (ii) and (ii') derived from silicon.

[0033] The silicon-derived polymer forms a continuous, random, three-dimensional porous network in which the organic components are embedded.

[0034] With regard to the cathode layer, the organic polymer consists in particular of a polymer (i) having SH functional groups and a polymer (iii) having SO 3 H functional groups.

[0035] In the cathode layer, the ratio of the concentration of SO3H functional groups to the concentration of SH functional groups is generally 0.5 to 4, preferably 1 to 4.

[0036] As regards the anode layer, the organic polymer consists in particular of a polymer (iii') having SO3H functional groups.

[0037] As regards the cathode layer and the anode layer, the inorganic polymer consists in particular of polymers (ii) and (ii') respectively derived from silicon.

[0038] According to one embodiment:

[0039] - in the cathode layer, polymers (ii), (iii) and (i) are present in a ratio of 1:2:1, and

[0040] - In the anode layer, polymers (ii') and (iii') are present in a ratio of 1:2.

[0041] As polymer (i) having a mercapto functional group (—SH), mention may be made in particular of (3-mercaptopropyl)trimethoxysilane (MPTMS) of the following formula:

[0042]

[0043] As polymers (ii) and / or (ii'), mention may be made of silicon derivatives of the following formula, such as tetraethyl orthosilicate (TEOS) or tetramethyl orthosilicate (TMOS):

[0044]

[0045] The inorganic polymer (ii) and / or (ii') may also be a derivative of the Nafion type, or a sulfonated polyether

[0046] The inorganic polymer provides the backbone of the membrane.

[0047] As polymers (iii) and / or (iii′) having SO 3 H functional groups, mention may be made in particular of CSPTC (2-(4-chlorosulfonylphenyl)ethyltrichlorosilane) of the following formula:

[0048]

[0049] According to an alternative embodiment of the polymer mixture discussed above, the organic and inorganic components are co-condensed: the silicon polymer forms a network to which the organic polymer is grafted.

[0050] According to this embodiment, polymers (i), (ii) and (iii) on the one hand and polymers (ii') and (iii') on the other hand are copolymerized to form an organic-mineral copolymer, ie a copolymer comprising both an organic component and a mineral component.

[0051] Thus, depending on the cathode or anode layer, the silica derivative may be functionalized with SH and / or SO3H functional groups.

[0052] Identical or different polymers (i), (ii), (ii'), (iii), (iii') can hereby be selected respectively from silicon-derived (co)polymers having SH functional groups and / or SO3H functional groups.

[0053] In any of the above embodiments, the blended or copolymerized polymers contain both a mineral component (polymer (ii) or (ii') derived from silicon) to achieve network rigidity and an organic component (polymer (i), (iii) or (iii')) whose SH and / or SO3H functional groups provide mobile protons (for polymer (i), optionally after hydrolysis of the SH functional groups).

[0054] Typically, the anode layer and cathode layer may also contain one or more non-conductive (to) polymers to ensure the mechanical properties of the membrane. These polymers are known and are generally used for this purpose in membranes. Therefore, as non-conductive polymers, polyvinylidene fluoride (PVDF), polyhexafluoropropylene (HFP), their mixtures and / or their copolymers poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) can be mentioned, which corresponds to the following formula:

[0055]

[0056] The cathode layer and the anode layer of the membrane according to the invention may further comprise one or more identical or different organic or inorganic additives, depending on the layer.

[0057] Additives conventionally used in proton-conducting membranes may also be considered here. As additives, PEO (polyethylene glycol) and OFP (2,2,3,3,4,4,4,5,5-octafluoro-1-pentanol (OFP)) having the following formulae may be mentioned in particular:

[0058]

[0059] PEO improves the conductivity and mobility of the PVDF-HFP chains, while OFP improves the affinity between PVDF-HFP (due to its carbon chains with fluorine atoms) and the inorganic components (due to the presence of hydroxyl functional groups).

[0060] The total thickness of the film according to the invention is generally from 5 to 150 μm, typically from 15 to 40 μm.

[0061] According to one embodiment, the cathode layer is thinner than the anode layer. Typically, the cathode layer has a thickness of 5 to 10 μm.

[0062] According to one embodiment, the anode layer and / or cathode layer consists of polymer fibers of the above-mentioned mixed or copolymerized polymers.

[0063] The fibers are randomly mixed together to create a porous three-dimensional network.

[0064] Typically, these fibers have an average diameter of between 100 nm and 10 μm. This diameter can be adjusted in particular according to the diameter of the nozzle of the electrospinning device used during their production.

[0065] According to another object, the invention also relates to a fuel cell comprising a double-layer membrane according to the invention.

[0066] In such a cell, the membrane according to the invention is coated on the outer face of the cathode layer with a cathode catalyst layer and on the outer face of the anode layer with an anode catalyst layer.

[0067] According to one embodiment, the cathode catalytic layer comprises polymers (i) and (iii), and the anode catalytic layer comprises polymer (iii'), said polymers (i), (iii) and (iii') being as defined above.

[0068] exist Figure 2 An explanatory schematic diagram of the structure of a battery according to the present invention is shown in FIG.

[0069] like Figure 2 As shown:

[0070] A fuel cell consisting of an anode (5') and a cathode (5) is separated by a proton exchange membrane (3), said membrane (3) comprising a cathode layer (1) on the cathode side and an anode layer (2) on the anode side.

[0071] The thickness e1 of the cathode layer (1) is usually 3 to 15 μm, in particular 5 to 10 μm, preferably 5 to 7 μm. The thickness e2 of the anode layer (2) is usually 5 to 40 μm, in particular 10 to 30 μm, preferably 10 to 20 μm.

[0072] On the cathode-side outer face of the membrane (3), the cathode layer (2) is coated with a cathode catalytic layer (4).

[0073] On the outer face of the membrane (3) on the anode side, the anode layer (2) is coated with an anode catalyst layer (4').

[0074] The cathode (4) and anode (4') catalyst layers comprise proton conductors (ionomers) (11) and (21), respectively, in which are distributed catalytic particles (12) and (22), respectively. Typically, these catalytic particles consist of platinum (Pt) particles on a carbon support.

[0075] The cathode layer (1) contains in particular SH and SO3H functional groups. These SH and SO3H functional groups are also present in the cathode catalytic layer (4), thereby defining a region (1') functionalized with SH functional groups, which consists of the cathode layer (1) and the cathode catalytic layer (4).

[0076] The anode layer ( 2 ) contains, in particular, SO 3 H functional groups, which are also present in the anode catalyst layer ( 4 ′).

[0077] According to another object, the present invention also relates to a method for preparing a membrane according to the present invention, said method comprising:

[0078] - forming fibers constituting the cathode layer by electrospinning a solution comprising at least one polymer (i) having a thiol functional group (-SH) and at least one polymer (iii) having a SO3H functional group;

[0079] - forming fibers constituting the anode layer by electrospinning a solution comprising at least one polymer (iii′) having a SO 3 H functional group;

[0080] - Separately shaping the anode layer and cathode layer of the obtained fiber;

[0081] - applying the cathode layer onto the anode layer.

[0082] According to one embodiment, the solution is a sol-gel solution.

[0083] The method according to the invention combines sol-gel chemistry and electrospinning technology and allows obtaining at high temperatures and at a relative humidity of 90% with a relative humidity of 1.5 %. The membrane is similar to a proton-conducting membrane that has anisotropic mechanical properties.

[0084] The morphology of the electrospun membrane according to the present invention can be modulated depending on the parameters of the sol-gel synthesis (e.g. with or without additives) and / or the electrospinning step, such as relative humidity, applied electric field, temperature, electrode rotation speed, etc.

[0085] Electrospinning ("electrospinning") or electrostatic spinning is a method for producing fibers that uses electricity to pull charged polymer filaments. The technology is based on applying a sufficiently high voltage to small droplets of polymer in liquid form (solution or molten state): the liquid phase is charged, and the electrostatic repulsion forces are now opposite to the surface voltage, forcing the droplets to stretch until a critical point (eruption point or "Taylor cone"), at which a liquid stream ejects from the surface. If the molecular cohesion of the liquid is high enough, the stream does not break and a jet filled with liquid is formed. The jet is now elongated by a process caused by electrostatic repulsion until it is finally deposited on the ground of the collector. The elongation and thinning of the fibers leads to the formation of uniform "electrospun" fibers with nanometer diameters.

[0086] The sol-gel method includes the establishment of an oxide network by a molecular precursor (usually a metal alkoxide) through an inorganic polymerization reaction in a solution. This polymerization is carried out by hydrolysis and condensation. The hydrolysis step is usually carried out with a catalyst, which can be an acid or a base. It includes a reaction between water and a precursor to generate a hydroxyl-type reactive functional group in the form of a solution called a sol. Condensation includes converting the hydroxyl functional group to cause gelation and forming a gel, the viscosity of which increases over time to form a mineral macromolecular network. The "gel" phase in the sol-gel method is defined and characterized by a solid 3D "skeleton" included in the liquid phase. The solid phase is usually a condensed polymer sol in which the particles have been entangled to form a three-dimensional network.

[0087] According to one embodiment, the solution is prepared by mixing the (co)polymer in an organic solvent in the presence of a mineral sol-gel precursor.

[0088] Therefore, the obtained sol-gel can be characterized as a “hybrid sol-gel”, to which the organic molecules have been added during the synthesis and are preserved in the final material.

[0089] Typically, the mineral precursor is silica functionalized with sulfonic acid (SO3H-SiO2).

[0090] Typically, the concentration of the (co)polymer in the solution is 5-20% by weight.

[0091] The sol-gel synthesis can be advantageously carried out at room temperature. The temperature, pH, the type of precursors and the type of solvent as well as the concentration of the reagents can generally be adjusted.

[0092] Thus, the membrane obtainable by the process of the present invention comprises a continuous random porous 3D network of electrospun mixed (co)polymer fibers, BRIEF DESCRIPTION OF THE DRAWINGS

[0093] Figure 1 An electrospinning process is described for the synthesis of the fibers constituting the membranes according to the invention.

[0094] Figure 2 The structure of a fuel cell comprising a membrane according to the invention is shown.

[0095] Figure 3 Shown is an EDX analysis showing the distribution of different elements in the fiber: oxygen (a), silicon (b), sulfur (c) and fluorine (d).

[0096] Figure 4The variation of proton conductivity as a function of relative humidity and the presence or absence of self-regenerating SH functional groups is described for mixed electrospun membranes comprising polymers (ii') and (iii') in a 1:2 ratio (TEOS:CSPTC (1:2)) or for mixed electrospun membranes comprising polymers (i), (ii) and (iii') in a 1:2:1 ratio of (ii):(iii):(i) (TEOS:CSPTC:MPTMS (1:2:1)).

[0097] Figure 5 Shown is the variation of proton conductivity as a function of relative humidity for the hybrid electrospun membranes after accelerated degradation testing and as a function of the presence or absence of self-regenerating SH functional groups: for membranes comprising polymers (ii') and (iii') in a 1:2 ratio (TEOS:CSPTC (1:2)) or for membranes comprising polymers (i), (ii) and (iii') in a 1:2:1 ratio of (ii):(iii):(i) (TEOS:CSPTC:MPTMS (1:2:1)).

[0098] Figure 6 Photographs of the two surfaces of a bilayer membrane are shown: the left picture represents the anode side (conductive anode layer) and the right picture represents the cathode side (self-regenerating cathode layer).

[0099] Figure 7 Scanning electron microscope (SEM) images are shown showing the structure of a cross section of a conductive anode layer (a), a self-regenerating cathode layer (b), and a bilayer membrane (c).

[0100] Figure 8 The variation of the conductivity as a function of relative humidity is shown for the anode layer (a) and the cathode layer (b). DETAILED DESCRIPTION

[0101] Example :

[0102] 1. Synthesis and Characterization

[0103] The cathode layer solution :

[0104] The sol-gel solution was prepared by pre-dissolving the non-conductive polymer (PVDF-HFP) in dimethylformamide (DMF) (600 mg PVDF-HFP in 700 mL DMF). Additives (PEO: polyethylene glycol and OFP: 2,2,3,3,4,4,5,5-octafluoro-1-pentanol) were then added (340 mg PEO and 60 mg OFP). Then, silicon precursors (TEOS (tetraethyl orthosilicate, 310 mg), CSPTC (2-(4-chlorosulfonylphenyl)ethyltrichlorosilane, 2.04 g, from a 50 mass % solution in dichloromethane) and MPTMS ((3-mercaptopropyl)trimethoxysilane, 310 mg) were added according to the different molar ratios tested, ending with the most reactive CSPTC. The solution was aged at 70° C. for 3 hours with stirring to prehydrolyze the silicon precursor. A homogeneous solution V2 was obtained, which contained SH and –SO3H functional groups and had a TEOS / CSPTC / MPTMS ratio of 1:2:1. Solutions with ratios of 1:2:2 and 1:1:1 were also prepared in this manner.

[0105] Anode layer solution :

[0106] The above operation was performed using the precursor mixture without MPTMS to obtain solution V1 (containing -SO3H functional groups).

[0107] Electrospinning :

[0108] Fibers were then prepared by electrospinning each of the obtained solutions V1 and V2.

[0109] The electrospinning equipment used (such as Figure 1 The device (shown) includes a syringe and a needle (ID=0.75 mm), a ground electrode and a commercial high-voltage unit (ES1a, Electrospinz). The needle is connected to the high-voltage unit, which can generate a positive DC voltage up to 40 kV.

[0110] Prepare two syringes containing a certain volume of solution V1 or solution V2 respectively. To obtain a total thickness of 20 μm, 0.15 ml of solution V1 and 0.075 ml of solution V2 are used. Each V1 and V2 solution is electrospun at 26 kV, and the flow rate depends on the ambient humidity. Generally, the relative humidity should be less than 60 ° C and the flow rate is about 0.025 mL.min -1 A steel needle was connected to the electrode of the high voltage cell and a grounded aluminum foil was placed 15 cm from the end of the needle to collect the different layers.

[0111] To make the second layer of film, the first syringe was replaced with a second syringe.

[0112] A white and flexible membrane was obtained. Finally, the proton exchange membrane was dried at 70 °C in air for 24 h. After drying, the EHS membrane was carefully peeled off from the aluminum foil. The thickness of the membrane depends on the volume amount injected into the electric field and can vary between 15-40 microns.

[0113] The two layers obtained in this way are Figure 6 as shown in .

[0114] Membrane analysis

[0115] The structure was studied by scanning electron microscopy, e.g. Figure 7 shown.

[0116] Scanning electron spectroscopy images of the surface and cross-section of the electrospun proton exchange membrane showed that the entangled fibers (D = 200 nm) were randomly organized in 3D space, defining an 85.4% continuous porous network. The thickness of the membrane was measured to be about 20 μm. EDX analysis of the fibers ( Figure 3 ) indicates that the elements O, F, S, and Si are evenly distributed on the surface, and no phase separation is found at the micrometer level.

[0117] 2. Nature

[0118] Calculations of water retention show that the TEOS:CSPTC:MPTMS (1:2:1) cathode layer is much less hydrophilic than the corresponding TEOS:CSPTC (1:2) anode layer (69.6% water vs. 141.9% water).

[0119] The self-regeneration properties of membranes comprising a cathode layer with –SH functional groups were analyzed.

[0120] like Figure 4 As shown in Figure 1, the change in proton conductivity as a function of humidity shows that the addition of self-regenerating reactive functional groups has little effect on the conductivity values ​​of the conventional membrane. However, the membrane containing -SH functional groups has better oxidation resistance, especially in the presence of H2O2, as shown in Figure 1. Figure 5 As shown, Figure 5 The conductivity retention after accelerated degradation testing is shown.

[0121] The effect of the –SO3H / SH functional group ratio on the physicochemical properties of the membranes was studied for different compositions:

[0122] For the anode layer, the following TEOS:CSPTC ratios were tested: 1:2, 1:3, 1:1 and 2:1.

[0123] For the cathode layer, the following TEOS:CSPTC:MPTMS ratios were tested: 1:2:1, 1:2:2, and 1:1:1.

[0124] exist Figure 8 The effect on conductivity is shown in Figure 8 The diagram shows the variation of the conductivity as a function of the moisture content for different mixed membrane compositions. The left diagram represents the variation of the conductivity as a function of the TEOS / CSPTC ratio and the right diagram represents the variation of the conductivity as a function of the amount of TEOS / CPSPTC / MPTMS. These experiments show that at 80°C, it is the values ​​of TEOS:CSPTC of 1:2 and TEOS:CSPTC:MPTMS of 1:2:1 that give the best results in terms of conductivity.

Claims

1. A proton exchange membrane for a fuel cell, the membrane comprising an anode face on the anode side and a cathode face on the cathode side, the membrane comprising two layers: a conductive and self-regenerating cathode layer providing the cathode face and comprising at least one polymer having SO3H functional groups (iii), and a conductive anode layer providing the anode surface and comprising at least one polymer having SO3H functional groups (iii'); The polymers (iii) and (iii') are the same or different; The membrane is characterized in that the cathode layer comprises at least one polymer (i) having a thiol functional group, ie -SH.

2. The film according to claim 1, wherein The cathode layer and / or the anode layer further comprise an inorganic polymer (ii) and / or (ii'), respectively; the polymers (ii) and (ii') are the same or different.

3. The film according to claim 1 or 2, wherein The polymer (i) having SH functional groups is obtained by polymerizing (3-mercaptopropyl)trimethoxysilane, namely MPTMS.

4. The film according to claim 2, wherein The polymers (ii) and / or (ii') are obtained by polymerizing tetraethyl orthosilicate, ie, TEOS, or tetramethyl orthosilicate, ie, TMOS.

5. The film according to claim 1 or 2, wherein The polymer (iii) and / or (iii') is obtained by polymerizing 2-(4-chlorosulfonylphenyl)ethyltrichlorosilane, namely CSPTC.

6. The film according to claim 1 or 2, wherein The cathode layer has a thickness of 3 to 15 micrometers.

7. The film according to claim 1 or 2, wherein The cathode layer has a thickness of 5 to 10 micrometers.

8. The film according to claim 1 or 2, wherein The cathode layer has a thickness of 5 to 7 micrometers.

9. The film according to claim 1 or 2, wherein The cathode layer has an increasing concentration gradient of SH functional groups from its inner face with the anode layer toward its outer face providing an interface with the cathode catalyst layer.

10. The film according to claim 2, wherein In the cathode layer, the molar ratio of polymers (ii), (iii) and (i) is 1:2:1, and In the anode layer, the molar ratio of polymers (ii') and (iii') is 1:

2.

11. A fuel cell comprising the membrane according to any one of claims 1 to 10, wherein the membrane is coated with a cathode catalyst layer on the outer face of the cathode layer and with an anode catalyst layer on the outer face of the anode layer.

12. The battery according to claim 11, wherein The cathode catalyst layer comprises polymers (i) and (iii), and the anode catalyst layer comprises polymer (iii').

13. A method for preparing a membrane according to any one of claims 1 to 10, comprising: - forming the fibers constituting the cathode layer by electrospinning a solution comprising at least one polymer having a thiol functional group, i.e. -SH, and at least one polymer having a SO3H functional group (iii); - forming fibers constituting the anode layer by electrospinning a solution comprising at least one polymer (iii′) having a SO 3 H functional group; - Separately shaping the anode layer and cathode layer of the obtained fiber; as well as - applying the cathode layer onto the anode layer.

Citation Information

Patent Citations

  • Hybrid silica polymer, method for production thererof, and proton-conducting material

    US20070213494A1

  • Fluoropolymer film

    CN107406549A

  • Proton-conductive film, process for producing the same, and fuel cell empolying the proton-conductive film

    CN1781162A

  • Polymer electrolyte film, film / electrode joining body and fuel cell

    JP2008171665A